2013
DOI: 10.1371/journal.pone.0072578
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Modulates Acetylcholine Release via Octopamine and CREB Signaling in Caenorhabditis elegans

Abstract: Animals change their behavior and metabolism in response to external stimuli. cAMP response element binding protein (CREB) is a signal-activated transcription factor that enables the coupling of extracellular signals and gene expression to induce adaptive changes. Biogenic amine neurotransmitters regulate CREB and such regulation is important for long-term changes in various nervous system functions, including learning and drug addiction. In Caenorhabditis elegans, the amine neurotransmitter octopamine activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 36 publications
2
19
0
1
Order By: Relevance
“…Decreases in DA are important for Ach-dependent nerve signaling shown in a C. elegans model (Allen et al, 2011, Suo and Ishiura, 2013). Donepezil, a piperidine derivative that inhibits the degradation of Ach, or an acetylcholinesterase inhibitor, can preserve Ach and DA levels in the AD model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreases in DA are important for Ach-dependent nerve signaling shown in a C. elegans model (Allen et al, 2011, Suo and Ishiura, 2013). Donepezil, a piperidine derivative that inhibits the degradation of Ach, or an acetylcholinesterase inhibitor, can preserve Ach and DA levels in the AD model.…”
Section: Discussionmentioning
confidence: 99%
“…DA metabolism is linked to microglial function (Farber et al, 2005), regulation of enzymatic modifications (Ara et al, 1998, Park et al, 2003, Belluzzi et al, 2012), glucose and insulin homeostasis (Williams et al, 2007), and acetylcholine (ACh) induced nerve transmission (Allen et al, 2011, Suo and Ishiura, 2013). When DA metabolism is altered, the subsequent OS results in the formation of cytotoxic downstream mediators such as LPO products and ROS.…”
Section: Introductionmentioning
confidence: 99%
“…Ub G76V -GFP degradation was previously monitored in C. elegans intestinal or hypodermal epithelia when this UFD substrate was expressed from either the sur-5 or col-19 promoter, respectively (Liu et al, 2011;Segref et al, 2011). We found that the neurotransmitter dopamine (DA), which is made by mechanosensory neurons in C. elegans and used to transmit information about surrounding environmental viscosity to the motoneurons so as to modulate feeding behavior (Sawin et al, 2000;Chase et al, 2004;Kindt et al, 2007;Suo & Ishiura, 2013), also functions to modulate Ub G76V -GFP turnover in epithelia. We found that the neurotransmitter dopamine (DA), which is made by mechanosensory neurons in C. elegans and used to transmit information about surrounding environmental viscosity to the motoneurons so as to modulate feeding behavior (Sawin et al, 2000;Chase et al, 2004;Kindt et al, 2007;Suo & Ishiura, 2013), also functions to modulate Ub G76V -GFP turnover in epithelia.…”
Section: Introductionmentioning
confidence: 99%
“…To confirm the requirement of cha-1 in the SIA neurons we used another transgene that drove cha-1 RNAi only in SIA using the ceh-17 promoter. ceh-17 also expresses in the ALA neuron but this neuron is not cholinergic, which should result in a SIA-specific knockdown of cha-1  (Duerr et al, 2008; Pereira et al, 2015; Pujol et al, 2000; Suo and Ishiura, 2013). Again, we measured flipping as before.…”
Section: Resultsmentioning
confidence: 99%
“…All constructs obtained from LR reactions were sequenced for verification. Sequences used for cha-1 RNAi were described previously (Suo and Ishiura, 2013). The following Gateway entry clones were constructed for this study:…”
Section: Methodsmentioning
confidence: 99%